2022
DOI: 10.3390/jcm11092583
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Multidisciplinary Spine Clinic on Time to Care in Patients with Chronic Back and/or Leg Pain: A Propensity Score-Matched Analysis

Abstract: Chronic back and leg pain are leading causes of disability worldwide. The purpose of this study was to compare the care in a unidisciplinary (USC) versus multidisciplinary (MSC) spine clinic, where patients are evaluated by different specialists during the same office visit. Adult patients presenting with a chief complaint of back and/or leg pain between June 2018 and July 2019 were assessed for eligibility. The main outcome measures included the first treatment recommendations, the time to treatment order, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Multiple studies have shown the benefits of multidisciplinary case conferences, tumor boards, and shared-decision making in the management of these conditions [ 9 , 10 ]. Naidu et al recently showed that a multidisciplinary spine clinic significantly reduced the utilization of surgery as a first treatment option and provided quicker times to injections for patients afflicted with chronic back and/or leg pain [ 11 ]. A systematic review of ten studies examining multidisciplinary approaches in spinal deformity found that these strategies significantly reduced operative time and complication occurrence [ 9 ].…”
mentioning
confidence: 99%
“…Multiple studies have shown the benefits of multidisciplinary case conferences, tumor boards, and shared-decision making in the management of these conditions [ 9 , 10 ]. Naidu et al recently showed that a multidisciplinary spine clinic significantly reduced the utilization of surgery as a first treatment option and provided quicker times to injections for patients afflicted with chronic back and/or leg pain [ 11 ]. A systematic review of ten studies examining multidisciplinary approaches in spinal deformity found that these strategies significantly reduced operative time and complication occurrence [ 9 ].…”
mentioning
confidence: 99%